Analysis of COD and BOD5 at the Inlet and Outlet of the Wastewater Treatment Plant (WWTP) at Hospital X - Sunardi; Fakhrizal Falah; Argoto Mahayana; Sumardiyono; Nur Hidayati; Soebiyanto; Mahardira Dewantara (Jurnal Serambi Engineering, 2024)
Hospitals are one of the service facilities that produce large amounts and quality of liquid waste that requires special attention because it contains hazardous materials for public health and the environment. This study aims to determine the quality of COD and BOD effluents in X Hospital. The type of research used is observational with a descriptive approach. The sampling technique used was purposive sampling, where wastewater samples were taken from two points, namely the inlet and the outlet of the WWTP. Based on the results of the laboratory analysis of the wastewater samples from Hospital X, it can be concluded that the average COD value at the inlet of the WWTP was 64.04 mg/L, while the average COD value at the outlet of the WWTP was 47.90 mg/L, and the average BOD value at the inlet was 12.69 mg/L, while the average BOD value at the outlet was 1.60 mg/L. All of these values are qualified according to the Hospital Activity Liquid Wastewater Quality Standards based on Central Java Province Regional Regulation No. 5 of 2012. It is expected that Hospital X will continue to maintain the wastewater treatment plant.